Molecular identification of LAB and yeasts from traditional sourdoughs and their impacts on the sourdough bread quality characteristics - Ayse Sevgili; Canan Can; Derya Isler Ceyhan; Osman Erkmen (Current Research in Food Science, 2023)
In this research, the LAB and yeast isolations and identifications of homemade traditional sourdoughs were investigated. Both LAB and yeasts were identified by the PCR method and used in the production of sourdough bread (SDB). Twelve types of SDB were produced from combinations of isolated LAB and yeasts. Eleven LAB and yests were identified from 36 sourdoughs. The most frequently isolated LAB species were Lactobacillus brevis (45.0%), Pediococcus acidilactici (20.0%) and Lactobacillus plantarum (18.3%) while other LAB species were isolated by only 1.7–3.5%. On the other hand, 27.5% of the isolates were Saccharomyces cerevisiae, which was followed by Pichia kudriavzevii (25.0%) and Kluyveromyces marxianus (12.5%). The total titratable acidity and pH of the sourdough ranged from 3.10 to 34.45% and from 4.05 to 4.80 respectively. High acceptable loaf height (7.2 cm), moisture (30.05%), dry matter (69.95%), volume (1370 cm3), specific volume (4.35 cm3 g−1) and sensory value (62 scores) were determined for SDB12. Isolated LAB is mainly composed of heterofermentative species (75%). Among the bread produced with the combination of LAB and yeasts, the SDB12 was the most preferred SDB in terms of sensory analysis and other quality characteristics. The use of homofermentative and heterofermentative LAB and yeast combinations provided high-quality SDB. This would be due to the symbiotic growth of these microorganisms. The use of L. plantarum by L. brevis and by other species resulted in high-quality SDB.